Determination of clinical outcome in mitral regurgitation with cardiovascular magnetic resonance quantitation - Myerson, S; d'Arcy, J; Christiansen, J; Dobson, L; Mohiaddin, R; Francis, J; Prendergast, B; Greenwood, J; Karamitsos, T; Neubauer, S (American Heart Association, 2016)
Background: Surgery for severe mitral regurgitation (MR) is indicated if symptoms or LV dilation/ dysfunction occur. However, prognosis is already reduced by this stage and earlier surgery on asymptomatic patients has been advocated if valve repair is likely, but identifying suitable patients for early surgery is difficult. Quantifying the regurgitation may help, but evidence for its link with outcome is limited. Cardiovascular magnetic resonance (CMR) can accurately quantify MR, and we examined whether this was associated with the future need for surgery. Methods and results: 109 asymptomatic patients with echocardiographic moderate or severe MR had baseline CMR scans and were followed for up to 8 years (mean 2.5±1.9 years). CMR quantification accurately identified patients who progressed to symptoms or other indications for surgery: 91% of subjects with regurgitant volume ≤55ml survived to 5 years without surgery compared to only 21% with regurgitant volume >55ml (p<0.0001); similar separation was observed for regurgitant fraction below and above 40%. CMR-derived end-diastolic volume index showed a weaker association with outcome (proportions surviving without surgery at 5 years: 90% for LVEDVi <100ml/m2 versus 48% for ≥100ml/m2) and added little to the discriminatory power of regurgitant fraction/volume alone. Conclusions: CMR quantification of mitral regurgitation was associated with the development of symptoms or other indications for surgery, and showed better discriminatory ability than ‘reference-standard’ CMR-derived ventricular volumes. CMR may be able to identify appropriate patients for early surgery, with the potential to change clinical practice, though the clinical benefits of early surgery require confirmation in a clinical trial.